Association Between Inflammation and Appetite in Healthy Community-Dwelling Older Adults—An enable Study - Chareh, Neshat; Kiesswetter, Eva; Kob, Robert; Hannink, Anne; Brandl, Beate; Skurk, Thomas; Hauner, Hans; Sieber, Cornel C.; Volkert, Dorothee (Frontiers in Aging, 2022)
Aging is associated with reduced appetite as well as a slight increase in pro-inflammatory status, which both might contribute to the development of malnutrition. We aimed to evaluate the association between inflammation based on serum C-reactive protein (CRP), and appetite in healthy community-dwelling older adults. In this cross-sectional study of 158 healthy and non-smoking persons (aged 75-85 years), appetite was assessed in personal interviews by a single question with five answer categories. As nobody reported (very) poor appetite, the remaining three categories were dichotomised into “(very) good” and “moderate” appetite. Fasting serum CRP was analysed according to standard procedures, values >5.0 mg/L were considered as inflammation. The association between inflammation and appetite was examined by binary logistic regression, unadjusted and adjusted for age, sex, waist circumference, leptin, depressive mood, number of medications, interleukin-6 and tumor necrosis factor-α. Appetite was very good in 27.8%, good in 58.9%, and moderate in 13.3% of participants. Inflammation was present in 10.8% overall, in 8.8% of those with (very) good and in 23.8% of those with moderate appetite (p= 0.038). In the unadjusted model, participants with inflammation were 3.2 times more likely to have moderate appetite (95%CI: 1.01–10.44, p= 0.047). In the adjusted model, the odds of having moderate appetite was 3.7 times higher in participants with inflammation, but no longer significant (95%CI: 0.77–18.55, p= 0.102). In healthy older people, we found hints for a potential association between increased levels of CRP and a slightly reduced appetite. More studies in larger samples are needed.